Fuzzy dependencies in approximation semantic based on the hedge algebras approach. - Ban, Đoàn Văn; Tuấn, Trương Công; Thắng, Đoàn Văn (Journal of Computer Science and Cybernetics, 2013)
In this paper, we study fuzzy dependencies among attributes, between the attributes and methods in a fuzzy object class basing on approximate semantic. Similarly in the clear/fuzzy relational database, we present the definition of fuzzy attribute dependency and fuzzy method dependency. Furthermore, we applied fuzzy dependencies to find quite approximate answers for Null queries on object-oriented database model with fuzzy information and uncertainty.